Change Management Strategies to Implement A Fingerprint Based Attendance System in Information Systems Department Using ADKAR Model - Endang Sulistiyani; Achmad Holil Noor Ali; Hanim Maria Astuti (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2020)
Information Systems Department has used fingerprints as a student attendance system. But its implementation is briefly, because there are still technical and non-technical problems in the system. Unfortunately, at this time, the fingerprint is only left installed in each classroom and the manual attendance system is reused. It can be seen that the unsuccessful project management is caused by problems in changing from the manual system to the fingerprint system. Based on the ploblems, Information Systems Department of ITS requires change management strategies to implement this system. The planning of change management strategy is initiated by analyzing the gap between the business processes of manual attendance system and of the fingerprint-based attendance system. The goal of this gap analysis is to identify the changes and the impacts which then let to an identification to the solution. The solution will be an input for the development of change management strategy using the perspectives of Awareness, Desire, Knowledge, Ability, Reinforcement (ADKAR) model. The strategy is then mapped according to Prosci’s state of change. The result from this research is a change management roadmap of the fingerprint system’s implementation. This roadmap contains three states of change, which covering current, transition, and future.